Trimelopter pterocarpum (Hyacinthaceae subfam. Ornithogaloideae), a new species from South Africa - Martínez-Azorín, Mario; Dold, Anthony P.; Crespo, Manuel B.; Crouch, Neil R. (Phytotaxa, 2026)
Our field exploration in South Africa revealed an undescribed species of Trimelopter, sharing diagnostic characters of the genus, including a single flattened leaf, tepals thick-textured, with a darker longitudinal central band, visible on both sides and associated with three to five aggregated medial veins and ovary trilobed in transversal section, each lobe, which corresponds to one carpel, showing two longitudinal, prominent keels, giving a six angled appearance. However, the new species clearly differs from the currently known species in the genus by distinct morphological characters, such as the filaments distinctly pinched along the middle, the ovary showing very prominent winged keels, comparatively large capsules that are distinctly winged, and large seeds. Here we describe Trimelopter pterocarpum, a new species based on plants occurring in karroid regions in southern-central South Africa east of Xamdeboo [Aberdeen]. A complete morphological description of the new species as well as data on ecology, distribution and differences with related species is provided.